A Comparative Study of the Effects of Lateral Wedge Insole Shoe Modification on the Patients with Knee Osteoarthritis (TAJ: Journal of Teachers Association, 2018)
Background: Knee osteoarthritis (OA) is the common form of disability in comparatively elderly patient. Lateral wedge shoe insole is an easy, simple and cost effective approach which can be applied as an adjunct to pharmacotherapy to treat the patients with OA knee. The objective of the study is to evaluate the effectiveness of using lateral wedge shoe insole on pain and physical functioning in patients with OA knee.Method: A randomized prospective study was carried out in the department of Physical Medicine and Rehabilitation, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh from January, 2012 to March, 2012. Patients with OA knee by American College of Rheumatology Criteria were selected. Two intervention groups were compared. In patients of Group-A (32 patients) were treated with aceclofenac100mg and, omeprazole20mg bid, and daily instructions of activities of daily living (ADLs), isometric quadriceps muscle strengthening exercise. Patients of Group-B were given lateral wedge shoe insole along with above treatment. The change between two weeks post intervention and baseline WOMAC (Western Ontario and McMaster Universities) subscale and scores were calculated. There were 4 visits and in each visit, patients were assessed for pain, stiffness and physical function by WOMAC index.Results: A total 65 patients with OA knee were included in this study. The mean age was 56.5± 10 years. Male to female ratio was 1.32:1. Comparison of mean pretreatment and 8th week post treatment WOMAC physical function subscale score in Group A (4.9 ± 1.2 vs. 2.4 ± 0.8) showed significant improvement and in Group B (4.3 ± 1.2 vs. 1.9 ± 0.5) which also shows significant improvement more than group A. The result was compared and student t-test was done to see the level of significance. Method was found significant after treatment (p